Immunoreactivity of the AAA+ chaperone ClpB from Leptospira interrogans with sera from Leptospira-infected animals - Krajewska, J.; Arent, Z.; Wieckowski, D.; Zolkiewski, Michal; Kedzierska-Mieszkowska, S. (My University, 2017)
Background: Leptospira interrogans is a spirochaete responsible for leptospirosis in mammals. The molecular mechanisms of the Leptospira virulence remain mostly unknown. Recently, it has been demonstrated that L. interrogans ClpB (ClpB(Li)) is essential for bacterial survival under stressful conditions and also during infection. The aim of this study was to provide further insight into the role of ClpB in L. interrogans and answer the question whether ClpB(Li) as a potential virulence factor may be a target of the humoral immune response during leptospiral infections in mammals. Results: ClpB(Li) consists of 860 amino acid residues with a predicted molecular mass of 96.3 kDa and shows multi-domain organization similar to that of the well-characterized ClpB from Escherichia coli. The amino acid sequence identity between ClpB(Li) and E. coli ClpB is 52 %. The coding sequence of the clpB(Li) gene was cloned and expressed in E. coli BL21(DE3) strain. Immunoreactivity of the recombinant ClpB(Li) protein was assessed with the sera collected from Leptospira-infected animals and uninfected healthy controls. Western blotting and ELISA analysis demonstrated that ClpB(Li) activates the host immune system, as evidenced by an increased level of antibodies against ClpB(Li) in the sera from infected animals, as compared to the control group. Additionally, ClpB(Li) was found in kidney tissues of Leptospira-infected hamsters. Conclusions: ClpB(Li) is both synthesized and immunogenic during the infectious process, further supporting its involvement in the pathogenicity of Leptospira. In addition, the immunological properties of ClpB(Li) point to its potential value as a diagnostic antigen for the detection of leptospirosis.
Citation: Krajewska, J., Arent, Z., Wieckowski, D., Zolkiewski, M., & Kedzierska-Mieszkowska, S. (2016). Immunoreactivity of the AAA plus chaperone ClpB from Leptospira interrogans with sera from Leptospira-infected animals. Bmc Microbiology, 16, 8. doi:10.1186/s12866-016-0774-8
Keywords: Clpb; Leptospira Interrogans; Leptospirosis; Molecular Chaperone; Pathogen; Protein